Greenland Inland Traverse (GrIT): 2010 Mobility Performance and Implications - Lever, James H (2011)
The National Science Foundation initiated the Greenland Inland Traverse (GrIT) to resupply science stations at NEEM and Summit via over-snow transport. The inaugural traverse in 2008, while successful, encountered mobility problems owing to steep slopes along the first 60 miles, soft snow along much of the route, and higher than expected towing resistance of the fuel sleds. With our guidance, GrIT implemented several changes to improve performance in 2010, and these changes were largely successful. Planned half-load shuttling reduced immobilizations on steep sections, omission of the steel fuel sled eliminated the worst-performing sled, and towing the fuel bladders two inline on long plastic sheets rather singly on separate sheets improved performance of the remaining fuel sleds. In addition, we instrumented the bladder sleds to quantify the expected dependence of towing resistance on sled-snow interface temperature. Sliding friction warms the sled and produces a thin meltwater layer that decreases towing resistance over cold snow. Furthermore, to assess benefits of artificially warming the sleds, one dual-bladder sled included electric heating blankets (optionally on or off) and the other included black wrappers to increase solar gain. This report summarizes GrIT10 performance, evaluates the changes implemented and assesses implications for future GrIT operations. DISCLAIMER: